Experimental Study Of Comparative Performance Between Three Types Of Photovoltaic Modules In Static And Dynamic Installations Under Penang Climatic Condition - Ghazali, Muhammad Azhar (2012)
This study response to the Malaysia’s Building Integrated Photovoltaic (MBiPV) Program, a collaboration program between Malaysian Government and United Nation Development Program (UNDP) to find ways to increase the efficiencies of photovoltaic technologies and to ensure it is applicable in Malaysian climate condition. With the solar tracking system, the efficiency of photovoltaic module is expected to increase under Malaysian climate condition. This study focuses on the three common types of solar panels available in the Malaysian market and compares the performance between dynamic (single axis time/date tracking) and static photovoltaic installation’s system according to each type of photovoltaic panels. The dynamic system in this experiment was designed to support the three types of PV panels which allowed it to move with single degree of freedom (horizontally) according to the sun’s orientation (sunrise to sunset) from east to west. The movement of PV panels allowed it to set perpendicularly toward the sun insolation (incoming solar radiation) so that solar rays can be optimized from morning until evening. While in static system, each type of photovoltaic panels was set 0o horizontally. The study found that poly-crystalline and mono-crystalline photovoltaic panel has shown better performance in dynamic system. However,amorphous solar module performed significantly better with static system installation compared to dynamic system under Malaysian climate condition. Thus, it will influence on building envelope as future possibilities in designing green building. In built environment, by replacing the conventional type of solar installation with solar tracking installation, it’s not only increase the performance of the PV panels installed but also, it can be integrate to the overall building design as part of Building Integrated Photovoltaic (BiPV) to perform specific function to the building envelope (e.g., provide shades on top of parking lot, minimize direct heat from sun at roof top, minimize direct sunlight for natural lighting).